Cognitive impairment in patients with hematological malignancies at a long-term period after the transplantation of allogeneic hematopoietic stem cells - D. E. Vybornykh; S. Yu. Fedorova; S. O. Khrushchev; M. Yu. Drokov; E. G. Gemdzhian; L. A. Kuzmina; E. N. Parovichnikova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
A comprehensive assessment of clinical, clinico-psychopathological, neurological, neuropsychological and instrumental examinations in a single study allows for a more detailed study of cognitive impairments in patients with CSC at a long-term period (12-15 months) after the transplantation of allogeneic hematopoietic stem cells.Purpose. Assessment of cognitive impairments in patients with hematological malignancies at a long-term period after the transplantation of allogeneic hematopoietic stem cells.Materials and methods. Clinical, psychopathological, clinical, psychological, neuropsychological, neurophysiological and neurovisual methods were used to examine 36 patients with various hematological malignancies in the period of 12-15 months after allo-HSCT. Statistical data analysis was performed using the methods of descriptive statistics, analysis of contingency tables and dispersive (with repeated measurements) analysis.Results and discussion. At a long-term period of the study (12-15 months), it was found that cognitive impairments are largely eliminated under the influence of a temporary factor, as well as the treatment of associated conditions (mental disorders, infectious complications, etc.). However, their level does not reach the normal (or close to them) values characteristics of the pre-transplant stage. Among the causes of this phenomenon, mention may be made of the organic lesions of the central nervous system, which are recorded during EEG, CEP, MRI / CT studies, and toxic encephalopathy due to exposure to chemotherapeutic and immunosuppressive drugs.Conclusion. The dynamics of cognitive impairments in general reflects the dynamics of the multifactor effects of various hazards accompanying the transplantation of allogeneic hematopoietic stem cells on the central nervous system. In this case, it can be stated with confidence that the allo-HSCT procedure in the overwhelming majority of cases does not lead to critical cognitive impairments.